The possible involvement of interleukin-6 in congestive heart failure in a postmenopausal woman with uterine fibromatosis - M. Ohta; N. Keira; S. Yoshida; R. Yasuda; Y. Tarumi; H. Tsuchiya; M. Kikai; T. Nomura; T. Tatsumi (IMR Press, 2020)
Interleukin-6 (IL-6) has been shown to contribute to the progression of myocardial damage and dysfunction in congestive heart failure. We report a case of a 53-year old woman with congestive heart failure that may have been caused by IL-6 secreting uterine leiomyoma. The woman developed progressive dyspnea, pleural effusion, and leg edema with a decreased left ventricular ejection fraction (LVEF). Imaging studies indicated uterine leiomyoma compressing the vena cava. Due to unresponsiveness to conventional medical treatment, she underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy to alleviate compression of the vena cava. After surgery, pleural effusion and leg edema completely resolved. Concomitant with the subsequent improvement of LVEF, a pre-operative serum IL-6 measurement of 36.2 pg/mL fell to 1.6 pg/mL postoperatively. Immunologically positive staining for IL-6 was demonstrated in the cytoplasm of most of the uterine leiomyoma cells. These findings suggest that IL-6 produced by leiomyoma cells may have been involved in the pathophysiological progression of heart failure and associated hemodynamic changes.